Penggunaan Model Zmijewski dan Model Grover dalam Memprediksi Kesulitan Keuangan pada Industri Otomotif yang Terdaftar di BEI Tahun 2014-2018 - Hana Tamara Putri; Muhammad Syukri (Universitas Batanghari Jambi, 2020)
This study aims to predict financial distress in the Automotive Industry listed on the Indonesia Stock Exchange in the 2014-2018 period, there are 13 companies that become research samples. Analysis of Prediction of Financial Distress is an early warning for management to be able to take anticipatory steps if the company indicates there are financial problems. The analysis tool used is the Zmijewski X Score and Grover Score methods and the Wilcoxon Test to see the differences between the two prediction models. The results showed that there were differences in predictions between the X Score Zmijewski model and the Grover Score, X Score detected there were 5 companies experiencing financial difficulties and Grover Score predicted there were 4 companies that indicated financial difficulties